A COMPARATIVE ANALYSIS OF NURALI KABUL’S “YESTERDAY” AND FAZIL ISKANDER’S “THE POET” - Nematjonova Nafisa Bohodirovna; Erkuziyeva Marjona (Bright Mind Publishing, 2025)
The article presents a comparative analysis of the short stories “Yesterday” by the Uzbek writer Nurali Kabul and “The Poet” by the Abkhazian author Fazil Iskander. The study aims to identify the shared and distinct artistic principles of the two writers, who belong to different national literatures yet are united by a common humanistic worldview. The research examines thematic concerns, artistic style, composition, and the system of imagery. Particular attention is given to issues of memory, moral choice, and the role of the individual within the sociocultural context. The author concludes that Kabul’s and Iskander’s works share a common aspiration to affirm the value of spiritual freedom and moral integrity in human life.
Keywords: Nurali Kabul, Fazil Iskander, comparative analysis, short story, memory, poetics, humanism, morality, artistic world.